Kiat Memberdayakan Fungsi Perpustakaan SDN 04 Tanjung Alai Sebagai Sumber Belajar Siswa - Oktavia, Dika; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this study were to describe (1) the function of library in SDN 04 Tanjung Alai as a source of student learning, (2) the factors causing low visitor Library SDN 04 Tanjung Alai, and (3) tips empower function SDN 04 Tanjung Alai Library as a students learning resource. Data were collected through observation and interviews with principals, teachers and librarians in SDN 04 Tanjung Alai. Data was analyzed through descriptive method. Tips which were done such as (1) by providing additional duties outside the classroom, (2) students are encouraged to make Mading (bulletin board) and the story, taken as a reference at the Library of SDN 04 Tanjung Alai, (3) provide a synopsis as studentsâ€™ assignment, and (4) show the interesting books to read. Keywords: school library; reading; student learning resources; empowerment of the library Â